Design and Installation Lightning Protection System to Protect Hybrid Solar Rooftop System - Narate Charlangsut; Nawin Rodrueang; Sakhon Woothipatanapan; Manat Boonthienthong; Papon Ngamprasert; Nattachote Rugthaicharoencheep (My University, 2023)
This article presents design and installation the lightning protection system for hybrid solar power generation system. In the event of lightning strikes in the area where the solar power generation system is installed on the roof, it may cause damage to the solar power generation system and related electrical systems. For this reason, the concept of designing and installing a lightning protection system has been developed according to the standards of the Engineering Institute of Thailand (EIT). Since the rooftop solar power generation system used in this work is installed on an irregularly shaped building. Therefore, this paper chooses to use the rolling sphere method to design a lightning protection system that is suitable for buildings with this shape. After completing the design and installation of the lightning protection system, measure the resistance of the ground electrode. The resulting resistance is approximately 0.2 ohms, (not exceed 5 Ohm), which corresponds to EIT standards. That is, the proposed lightning protection system is suitable for the application area that is the case study in this paper.
Keywords: Fire Detection and Safety Systems